Corruption In Indonesia, A Bibliometric Analysis - Akbar, Gugun Geusan (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to present a summary of research with corruption in Indonesia through a bibliometric analysis of published articles in journals, conferences, books, literature reviews, and reputable book chapters. The method used was an analysis of historical, descriptive, and exploration to conduct bibliometric analysis. The articles retrieved by using keyword “corruption” and “Indonesia” in Scopus database. It showed 91 publications that published in 1996 to 2019.Publish or Perish Ver. 4 software used to retrieve and analyze the data while Vos Viewer Ver. 7 used for bibliometric analysis.The analysis results showed that there is a trend in an increase in the number of publications, the number of authors and co-authors, and researchers countries after 2006. Likewise, the area of research about corruption in Indonesia has expanded. The Bulletin of Indonesian Economic Studies is the top journal that contributes to the literature in terms of publication productivity. The Journal of Political Economy Journal is the top journal that contributes to the highest number of citations.This study provides a systematic analysis of corruption research in Indonesia. Moreover, this research can be a useful guide for research and corruption prevention in Indonesia.